Patient experience with chronic obstructive pulmonary disease: a nationally representative demonstration study on quality and cost of healthcare services - Ghamari, Seyyed-Hadi; Mohebi, Farnam; Abbasi-Kangevari, Mohsen; Peiman, Soheil; Rahimi, Besharat; Ahmadi, Naser; Farzi, Yousef; Seyfi, Shahedeh; Shahbal, Nazila; Modirian, Mitra; Azmin, Mehrdad; Zokaei, Hossein; et al. (Frontiers in Public Health, 2023)
Introduction Due to insufficient data on patient experience with healthcare system among patients with chronic obstructive pulmonary disease (COPD), particularly in developing countries, this study attempted to investigate the journey of patients with COPD in the healthcare system using nationally representative data in Iran. Methods This nationally representative demonstration study was conducted from 2016 to 2018 using a novel machine-learning based sampling method based on different districts’ healthcare structures and outcome data. Pulmonologists confirmed eligible participants and nurses recruited and followed them up for 3 months/in 4 visits. Utilization of various healthcare services, direct and indirect costs (including non-health, absenteeism, loss of productivity, and time waste), and quality of healthcare services (using quality indicators) were assessed. Results This study constituted of a final sample of 235 patients with COPD, among whom 154 (65.5%) were male. Pharmacy and outpatient services were mostly utilized healthcare services, however, participants utilized outpatient services less than four times a year. The annual average direct cost of a patient with COPD was 1,605.5 USDs. Some 855, 359, 2,680, and 933 USDs were imposed annually on patients with COPD due to non-medical costs, absenteeism, loss of productivity, and time waste, respectively. Based on the quality indicators assessed during the study, the focus of healthcare providers has been the management of the acute phases of COPD as the blood oxygen levels of more than 80% of participants were documented by pulse oximetry devices. However, chronic phase management was mainly missed as less than a third of participants were referred to smoking and tobacco quit centers and got vaccinated. In addition, less than 10% of participants were considered for rehabilitation services, and only 2% completed four-session rehabilitation services. Conclusion COPD services have focused on inpatient care, where patients experience exacerbation of the condition. Upon discharge, patients do not receive appropriate follow-up services targeting on preventive care for optimal controlling of pulmonary function and preventing exacerbation.